Normal forgetting, impaired acquisition in memory for complex naturalistic scenes by fornix-transected monkeys. - Gaffan, D (1993)
As part of an earlier experiment three rhesus monkeys (Macaca mulatta) with fornix transection and three normal control monkeys had learned to discriminate among 320 naturalistic complex scenes. The fornix-transected animals had been much slower than the controls to reach criterion in learning this task, but eventually did so. The present experiment measured long-term forgetting of these scenes. Seven weeks after reaching criterion each animal was retested. All animals showed some forgetting of the scene discriminations they had learned. The amount forgotten was equal in the two groups. These results show that the slower learning of the scenes following fornix transection was not caused by accelerated forgetting. The present findings in fornix-transected monkeys are similar to previous findings in human amnesic patients.